Cell Penetrating Peptides Used in Delivery of Therapeutic Oligonucleotides Targeting Hepatitis B Virus - Bénédicte Ndeboko; Serge Thierry Omouessi; Brice Ongali; Augustin Mouinga-Ondémé (MDPI AG, 2020)
Peptide Nucleic Acid (PNAs) and small noncoding RNAs including small interfering RNAs (siRNAs) represent a new class of oligonucleotides considered as an alternative therapeutic strategy in the chronic hepatitis B treatment. Indeed, chronic hepatitis B virus (HBV) infection remains a major public health problem worldwide, despite the availability of an effective prophylactic vaccine. Current therapeutic approaches approved for chronic HBV treatment are pegylated-interferon alpha (IFN)-α and nucleos(t)ide analogues (NAs). Both therapies do not completely eradicate viral infection and promote severe side effects. In this context, the development of new effective treatments is imperative. This review focuses on antiviral activity of both PNAs and siRNAs targeting hepatitis B virus. Thus, we briefly present our results on the ability of PNAs to decrease hepadnaviral replication in duck hepatitis B virus (DHBV) model. Interestingly, other oligonucleotides as siRNAs could significantly inhibit HBV antigen expression in transient replicative cell culture. Because the application of these oligonucleotides as new antiviral drugs has been hampered by their poor intracellular bioavailability, we also discuss the benefits of their coupling to different molecules such as the cell penetrating peptides (CPPs), which were used as vehicles to deliver therapeutic agents into the cells.